Neutrophil-To-Lymphocyte Ratio (NLR) and Platelet-to-Lymphocyte Ratio (PLR) as Predictors of Mortality in Chronic Kidney Disease Patients Undergoing Hemodialysis - Roy Efendi Silaban; Nindia Sugih Arto; Mohammad Riza Lubis (Indonesian Journal of Global Health Research, 2025)
Chronic Kidney Disease (CKD) is associated with high mortality, especially among patients undergoing hemodialysis (HD). Inflammation markers such as the Neutrophil-to-Lymphocyte Ratio (NLR) and Platelet-to-Lymphocyte Ratio (PLR) have been linked to mortality prediction. This study aims to evaluate the role of NLR and PLR as mortality predictors in CKD patients undergoing HD at H. Adam Malik Hospital, Medan. This retrospective study analyzed CKD patients receiving HD from January to December 2023, aged 18-60 years, and undergoing routine HD for at least 3 months. Excluded were those with comorbidities, immunosuppressant use, or incomplete records. Data on demographics, laboratory values (including NLR and PLR), and mortality outcomes were collected. ROC curve and logistic regression analysis were used. Out of 108 patients, 35 (32.4%) died. The median NLR was significantly higher in the mortality group (7.89 vs. 3.41, p < 0.001), while PLR showed no significant difference. ROC analysis revealed NLR's moderate accuracy (AUC = 73.3%, cut-off = 5). Multivariate analysis identified coronary artery disease history, age, and creatinine levels as significant mortality factors. NLR is a moderate predictor of mortality in CKD patients undergoing HD, while PLR is not.